Signal detection for molecular MIMO communications with asymmetrical topology - Wu, Cong; Lin, Lin; Guo, Weisi; Yan, Hao (IEEE, 2020)
Molecular communication (MC) has attracted people’s attention due to its potential applications at the micro- to nano-scale. In MC, the transmission rate is usually very low due to the slow diffusion of information molecules and therefore multiple-input multiple-output (MIMO) system is introduced. However, severe interference occurs when the same types of information molecules are used at different transmission antennas. Up to now, most literature focuses on MIMO systems with symmetrical topology. In this paper, a molecular MIMO communication system with asymmetrical topology, where the number of transmission antennas is not equal to that of the reception antennas, is investigated. The zero-forcing (ZF) detection approach is proposed and discussed for three cases, i.e., the number of transmission antennas is smaller than, equal to and larger than the number of the reception antennas. Considering the inter-link interference (ILI) and the inter-symbol interference (ISI), the error probability of ZF detection is derived and comparisons are made with existing molecular MIMO detection method. Besides, the adaptive observation time for each reception antenna is derived for better performance. Numerical results show that ZF detection performs better than the existing molecular MIMO detection method when the ILI is large
Keywords: Error performance; Signal detection; Asymmetrictopology; MIMO; Molecular communication